The Role of Basal Cistern as Prognostic Factor in Head Injury Cases - Fath, Tri Putra Nuur; Suhendar, Agus; Kania, Nia; Wibowo, Agung Ary; Poerwosusanta, Hery; Abidin, Zainal; Huldani, Huldani (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2025)
Background and Objective: Head injury is a medical condition affecting various individuals around the world and is characterized by high mortality and morbidity rates. Several studies have shown that accurate management and appropriate interventions are required to achieve favorable outcomes. In this context, head CT scan has been reported to be the gold standard in diagnostic imaging for patients with head injury. In addition, head CT scan can be used to evaluate basal cistern, which is an area around the brain with a significant role in consciousness due to its close association with the brainstem. Several factors are known to influence prognosis of head injury treatment, including age, gender, severity of head injury, type of bleeding lesion, and the condition of basal cistern, which play a crucial role in the outcome of patients care. Therefore, this study aims to determine the role of basal cistern as a predictor of prognosis in cases of head injury. Subject and Method: The study procedures were carried out using the prospective observational method, and the sample population comprised 67 head injury patients at Ulin Regional General Hospital (RSUD) from February to April in 2024. Based on the inclusion and exclusion criteria, a total of 60 patients were selected as participants, and their primary data were collected. Subsequently, each variable's data was analyzed using SPSS with Chi-square and Spearman correlation tests. Results: Significant differences were observed between various variables, including 1) the type of bleeding lesion and the condition of basal cistern (p-value: 0.004), 2) action (surgery and non-surgery) and prognosis (p-value: 0.017), and 3) prognosis and the condition of basal cistern (p-value: 0.0001). Conclusion: Based on the results, basal cistern could be used as a predictor of prognosis in patients with head injury. In addition, the severity of head injury was closely related to the condition of basal cistern. The more severe head injury, the worse prognosis for patients. The results also showed that the type of bleeding lesion affected the condition of basal cistern